System-on-chip communication architecture: dynamic parallel fraction control bus design and test methodologies - Wang, N.; Bayoumi, M.A. (IET computers & digital techniques, 2007)
Modern system-on-chip (SOC) designs consist of numerous heterogeneous components (embedded CPUs, dedicated hardware, FPGAs, embedded memories and so on) integrated onto a single chip. The on-chip communication is becoming the bottleneck for these SOC designs, and efficient contention resolution schemes for managing simultaneous access requests to the communication resources are required to prevent system performance degradation. A new SOC on-chip communication architecture, Dynamic Parallel Fraction Control Bus, which offers an attractive solution for the problem and addresses shortcomings of existing communication architectures is presented. To demonstrate the benefits of the proposed architecture, several existing communication architectures were compared with the proposed architecture on the basis of two application prototypes. Through experimentation it has been shown that the proposed architecture not only exhibits both hardware simplicity and system performance improvements, but also produces better bus bandwidth control and scalability properties compared with the existing communication architectures.